2022
DOI: 10.1002/ncp.10905
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the use and tolerance of a pediatric and an adult commercial blenderized enteral formula through real‐world data

Abstract: Background: Home enteral nutrition (HEN) is frequently prescribed to individuals who cannot consume adequate food orally. Commercial blenderized enteral formulas (CBEF) containing real-food ingredients are becoming more popular and more widely available; however, the demographics of patients receiving these formulas have rarely been evaluated, and little data are available on patient tolerance in the community. Methods: US claims data were obtained for children and adolescents/adults who used the CBEF of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…According to a retrospective analysis of children and adolescents discharged on a prescribed BTF, GI symptoms substantially improved over baseline. 38 The percentage of patients reporting no GI symptoms increased from 35.6% to 83%, and those reporting two or more symptoms decreased from 31.6% to 2.3% after 2 weeks. Likewise, a monocenter small pediatric study documented 100% resolution of diarrhea and improvements in vomiting after transition to BTF.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to a retrospective analysis of children and adolescents discharged on a prescribed BTF, GI symptoms substantially improved over baseline. 38 The percentage of patients reporting no GI symptoms increased from 35.6% to 83%, and those reporting two or more symptoms decreased from 31.6% to 2.3% after 2 weeks. Likewise, a monocenter small pediatric study documented 100% resolution of diarrhea and improvements in vomiting after transition to BTF.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have found similar results. According to a retrospective analysis of children and adolescents discharged on a prescribed BTF, GI symptoms substantially improved over baseline 38 . The percentage of patients reporting no GI symptoms increased from 35.6% to 83%, and those reporting two or more symptoms decreased from 31.6% to 2.3% after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most participants in the present study considered blended feeding to be an option for adults requiring tube‐feeding following stroke. Their responses indicated an understanding of the potential benefits (e.g., gastrointestinal improvements and QoL) that have been described in other studies, 24,30 as well as the conditions needed for this to be feasible. The potential concerns described by participants in the present study, including nutritional inadequacy, microbial risk and tube‐blocking, have been noted previously 31 .…”
Section: Discussionmentioning
confidence: 94%